PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR SISWA TENTANG GETARAN DAN GELOMBANG - Muhammad Najamuddin; Haratua Tiur Maria Silitonga; Hamdani Hamdani (Universitas Tanjungpura, 2021)
AbstractThis study aims to improve student learning outcomes by using a guided inquiry modelon vibration and wave at SMP Negeri 24 Pontianak. The form of this research is pre-experimental design with one group pretest-posttest design. The sample consisted of 33students of class VIII E who were selected through non-probabilty techniques. Theresearch instrument was a multiple choice test consisting of 10 questions and 3 essayquestions. The results of this study consisted of: 1) There were differences in learningoutcomes before and after the application of the inquiry guide model with an averagepretest score of 28.67 and an average post-test score of 73; 2) There was an increase instudent learning outcomes after using the guided inquiry model on vibration and wavematerial, namely 44.33 (moderate category); 3) the effect size on the use of guidedinquiry models in learning activities is 2.94 (high category). The use of guided inquirymodels is expected to be an alternative in improving physics learning outcomes.Keywords: Application, Vibration and waves, Learning Outcomes, Model GuideInquiry Learning.